Market Risk and Bank Specific Determinants of Commercial Banks in Malaysia - Ahmad Zolkifli, N.; Jonar, H.; Abdul Hamid, M. (Universiti Sains Islam Malaysia, 2024)
Market risk is one of the important risks in banking system. With a myriad number of products, market risk happens when change in net asset value due to changes in equity, commodity prices and exchange rate. This paper is an attempt to identify the factors that determine market risk in bank and to compare that risk determinants between conventional and Islamic banking systems in Malaysia. The unique duality banking system in Malaysia, namely the conventional and Islamic banking system would provide comprehensive determinants of market risk in banking sector. The dataset is constructed from 21 conventional banks and 16 Islamic banks with the year of observation within 2008-2014. Total loan/ financing, loan loss provision, total equity, GAP, interest expenses, short term investment, size, non- interest income and management efficiency are factors that were used in this study. Employing panel data analysis, the result revealed that GAP has strong relationship with market risk. Our findings are not only significant to both bank managers as well as investors, since they the findings will enable them to fully assess the effects of different strategic choices on a bank's risk profile but also contributing in terms of enriching and enhancing literature on market risk management of Islamic and conventional banks. Establishment of a comprehensive market risk management system in both banking system should be a prerequisite as it contributes to overall risk management system of the bank.